Novel propane-free mixed refrigerant integrated with nitrogen expansion natural gas liquefaction process for offshore units. (1st January 2022) - Jin, Chunhe; Yuan, Yilong; Son, Heechang; Lim, Youngsub
Abstract: The presence of propane inventory in offshore liquefaction processes increases the concerns for platform safety. To address this, we propose a novel liquefaction process that integrates propane-free mixed refrigerant and nitrogen expander cycles (MR-N2 ). The proposed design adopts the advantages of both nitrogen expander and single mixed refrigerant (SMR) processes. The process was rigorously simulated using Aspen HYSYS, and the specific energy consumption was optimized as an objective function using the genetic algorithm technique. Additionally, the MR-N2 process was investigated using exergy and sensitivity analyses to compare the obtained results with those of the previous studies. The results verify that both liquefaction and exergy efficiencies are improved by 27.15% and 14.92%, respectively, in comparison with those of the base case. Moreover, the MR-N2 process exhibits enhanced energy efficiency compared to that of the various existing nitrogen expander-based processes. The energy savings of the proposed method varies between 3.2% and 61.7%, and the cycle capacity is 22.43% better than that of the SMR process. Highlights: Propane-free mixed refrigerant with nitrogen expander (MR-N2 ) liquefaction process for offshore units. Energy consumption and exergy analysis are investigated. The process combined advantages of both the MR and nitrogen expander processes. Results verify MR-N2 improvement in liquefaction and exergy efficiencies. MR-N2 process can be applied in offshore liquefaction processes.